2020
DOI: 10.1371/journal.pone.0230936
|View full text |Cite
|
Sign up to set email alerts
|

Biodiverse food plants in the semiarid region of Brazil have unknown potential: A systematic review

Abstract: Food biodiversity presents one of the most significant opportunities to enhance food and nutrition security today. The lack of data on many plants, however, limits our understanding of their potential and the possibility of building a research agenda focused on them. Our objective with this systematic review was to identify biodiverse food plants occurring in the Caatinga biome, Brazil, strategic for the promotion of food and nutrition security. We selected studies from the following databases: Web of Science,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…After analysing all of the items, the studies received one point for each criterion met in both assessment tools. Based on these grades, we used the evaluation criteria developed by Jacob, Araújo de Medeiros and Albuquerque [14] to categorize the quality of the studies. These criteria were: strong – when the study met more than 80 % of the criteria; moderate – from 50–80 %; and weak/poor – less than 50 %.…”
Section: Methodsmentioning
confidence: 99%
“…After analysing all of the items, the studies received one point for each criterion met in both assessment tools. Based on these grades, we used the evaluation criteria developed by Jacob, Araújo de Medeiros and Albuquerque [14] to categorize the quality of the studies. These criteria were: strong – when the study met more than 80 % of the criteria; moderate – from 50–80 %; and weak/poor – less than 50 %.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the interest in bioactive compounds, this plant’s fruit also has a high nutritional potential ( 25 ). A previously published detailed metabolic profile of the ethanol extract of S. obtusifolium leaves revealed saponins and flavonoids as the main constituents.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when reviewing studies concerning BFP in the Brazilian Caatinga, one of us identified local consumption of an UFP (mucunã), considered toxic because of chemical composition studies (Grant et al 1986), (Dioclea grandiflora Mart. ex Benth) (Jacob et al 2020). Mucunã seeds likely contain small molecular weight components that cause its toxicity and which can be eliminated through exhaustive dialysis (Grant et al 1986).…”
Section: An Overview Of the Challenges Involved In Biodiverse Food Pl...mentioning
confidence: 99%
“…In this chapter, our focus is on biodiverse food plants. The definition of biodiverse food plants (BFP) involves the agricultural diversity of conventional crops cultivated locally (e.g., varieties of beans, rice, corn, banana), together with unconventional food plants (UFP), (usually native, neglected, and rarely available in the marketplace) (Jacob and Albuquerque 2020). Despite the potential of these plants to promote sustainable food systems and diets, when we review the literature in dietary assessment studies, we notice a gap in methods for gathering and assessing the intake of these plants.…”
Section: Introductionmentioning
confidence: 99%